2017
DOI: 10.1111/cup.13055
|View full text |Cite
|
Sign up to set email alerts
|

TNFα and IL‐17A are differentially expressed in psoriasis‐like vs eczema‐like drug reactions to TNFα antagonists

Abstract: Background Tumor necrosis factor α (TNFα) blocking drugs are in use for a wide range of autoimmune disorders. In up to 5% of patients, this class of drugs produces puzzling cutaneous side effects that are the subject of this investigation, namely psoriasiform and eczema‐like skin inflammation. These side effects can occur after any time of treatment and regardless of the underlying disorders. The exact pathophysiology is as yet unknown. Methods A total of 33 patients (19 female, average age 52 years) who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Interleukin 17 (IL-17) and 22 (IL-22), derived from Th17, are involved in the pathogenesis of anti-TNF-induced psoriasiform reactions, and higher expression of Th17 cells has been observed in more severely affected patients, who respond well to the anti-IL-12/23 ustekinumab. 30,31 However, exacerbation of the previous psoriasiform reactions during ustekinumab therapy have been described. 32 Vedolizumab, a gut-specific α4β7 integrin inhibitor, approved for both Crohn's disease and ulcerative colitis, has shown promising results in a few cases of anti-TNF-induced psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 17 (IL-17) and 22 (IL-22), derived from Th17, are involved in the pathogenesis of anti-TNF-induced psoriasiform reactions, and higher expression of Th17 cells has been observed in more severely affected patients, who respond well to the anti-IL-12/23 ustekinumab. 30,31 However, exacerbation of the previous psoriasiform reactions during ustekinumab therapy have been described. 32 Vedolizumab, a gut-specific α4β7 integrin inhibitor, approved for both Crohn's disease and ulcerative colitis, has shown promising results in a few cases of anti-TNF-induced psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, such as IL‐4, IL‐6, IL‐13, IFN‐γ, TNF‐α, CCL17 and CXCL9 that are released by T lymphocytes and mononuclear macrophages may participate in the occurrence and development of ADRs . TNF‐α and IFN‐γ are the key cytokines in SJS/TEN .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years a growing number of studies have revealed the association of psoriasis with other comorbidities, especially with CVD [50][51][52][53][54][55]. The risk of myocardial infarction and cerebrovascular disease is increased in psoriasis and correlates with disease severity.…”
Section: Adipocyte Macrophagementioning
confidence: 99%